An Efficient and Accurate Algorithm for Electromagnetic Wave Propagation Modeling Based on Wavelet Transforms (2024)
In this article, a comprehensive analysis of the approach known as Split-Step Wavelet Parabolic Equation (SSW-PE) in modeling radio wave propagation is presented. The SSW-PE introduces innovations, such as the application of narrow-angle and wideangle approaches, referred to as NAPE and WAPE, respectively. Furthermore, the SSW-PE demonstrates the incorporation of refractivity variations, modifications in terrain modeling for better representation, and considerations of surface boundary conditions. In addition to its innovative aspects, this study aims to provide a complete guide for effectively replicating the algorithm, thereby promoting the advancement of propagation studies using wavelets. The effectiveness and applicability of this approach are validated through comparative studies with well-established solutions, including the Discrete Mixed Fourier Transform (DMFT) version of the Split-Step Parabolic Equation (SSPE) method. Comparisons with measurements from real propagation cases are also conducted. Statistical analysis confirms the innovative potential of the SSW-PE algorithm, which also offers computational efficiency for rapid and consistent simulations. Thus, this article contributes to a comprehensive and innovative analysis, providing tangible resources for the research community interested in expanding this methodology.